Influence of the Activator Concentration and Solid/Liquid Ratio on the Strength and Shrinkage Characteristics of Alkali-Activated Slag Geopolymer Pastes - Zikai Xu; Jinchao Yue; Guanhong Pang; Ruixia Li; Peng Zhang; Shengtang Xu (Advances in Civil Engineering)
Geopolymers have distinct advantages such as having energy-saving properties, being an environmentally protective material, and having high mechanical strength and durability. However, the shrinkage of the geopolymer materials is one of the major problems to affect its practical application. In this study, blast furnace slag-based geopolymer pastes were prepared using sodium silicate and sodium hydroxide as activators to investigate the effect of the activator concentration and solid/liquid ratio on strength and shrinkage properties. For a better understanding of the reaction mechanism and microstructure of the geopolymer pastes, a multitechnique approach including scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectra was carried out. The results showed that the geopolymers compressive strength increased significantly as the activator concentration increased. The increase in activator concentration first increased the flexural strength and then decreased and reached the maximum when the activator concentration was 40%. A higher activator concentration, as well as a lower solid/liquid ratio, generally led to serious geopolymers drying shrinkage. These findings are expected to be ascribed from the changes in the content of the alkali-activated product (i.e., hydrate calcium aluminosilicate), which depends on the activator concentration. The increase in C-A-S-H gel (hydrate calcium aluminosilicate) compacts paste densifiers but causes shrinkage fracture concerns. These results provide an appropriate proportion for alkali-activated slag geopolymer pastes with better mechanical strength and antidry-shrinkage cracking properties, which are beneficial for the further applications of geopolymer materials.